Colouring Atlas of Human Anatomy - Chin, Edwin
This fully illustrated guide to the human body in which the student colors in the body's structural components includes 100 full-page drawings, each with a facing-page textual description and a labeling key that corresponds to the numbered anatomical structures in the illustration. This coloring atlas follows the standard sequence of topics in most beginning anatomy courses. The book is an excellent supplement to Winegard, THE HUMAN BODY